2017
DOI: 10.1073/pnas.1706915114
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ is a master checkpoint regulator of cytokine-induced differentiation

Abstract: Cytokines are protein mediators that are known to be involved in many biological processes, including cell growth, survival, inflammation, and development. To study their regulation, we generated a library of 209 different cytokines. This was used in a combinatorial format to study the effects of cytokines on each other, with particular reference to the control of differentiation. This study showed that IFN-γ is a master checkpoint regulator for many cytokines. It operates via an autocrine mechanism to elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 42 publications
0
37
0
2
Order By: Relevance
“… 47 IFN-γ induces the expression of PD-L1, through increasing STAT1 signaling and decreasing STAT3 activation. 48 IFN-γ can also upregulate the expression of other immune suppressive molecules. 49 In our study we found a strong positive correlation of IFNG with STAT1 mRNA expression, while in both cohorts, a strong correlation was detected between IFNG and the immune suppressive molecule CTLA4.…”
Section: Discussionmentioning
confidence: 99%
“… 47 IFN-γ induces the expression of PD-L1, through increasing STAT1 signaling and decreasing STAT3 activation. 48 IFN-γ can also upregulate the expression of other immune suppressive molecules. 49 In our study we found a strong positive correlation of IFNG with STAT1 mRNA expression, while in both cohorts, a strong correlation was detected between IFNG and the immune suppressive molecule CTLA4.…”
Section: Discussionmentioning
confidence: 99%
“…Ribechini et al found that GM-CSF altered the signaling pathway of IFN-γ allowing it to differentiate monocytes into MDSCs ( 92 ). In a recent article by Zha et al they found that IFN-γ was able to suppress the functions of gp130 cytokines, particularly the ability of OSM, to differentiate mesenchymal stem cells through the upregulation of STAT1, concomitant decrease in STAT3 activation, and internalization of the gp130 receptor ( 95 ). Thus, IFN-γ can both be altered by additional cytokine signaling as well as regulate the signaling pathways of other cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…ИФН видоспецифичны, обладают широким спектром свойств, в т.ч. антивирусными, иммунорегуляторными, антипролиферативными свойствами, и участвуют в регуляции экспрессии клеточных генов организма [29,34,47,51]. Все клетки организма в той или иной степени обладают способностью вырабатывать ИФН.…”
Section: Interferon Status As a Methods Of Determination Of Nonspecifiunclassified
“…ИФН II типа характеризуется иммунным ИФН-γ [51]. Индукторами ИФН-γ являются Т-клеточные митогены лектины, оксиданты, антилимфоцитарные сыворотки, фрагменты иммуноглобулинов антилимфоцитарных сывороток, специфические антигены и аллоантигены, участвующие в процессе распознавания клеток, большинство микроорганизмов, многие иммуномодуляторы, соли тяжелых металлов.…”
Section: Interferon Status As a Methods Of Determination Of Nonspecifiunclassified